Assessment of availability of visual inspection with acetic –acid (VIA) requirements for cervical cancer screening in secondary health care institutions of Kaduna State, Nigeria - Musa, Umar; Balarabe, Fatima; Chado, Mohammed Alfa; Ladan, Muhammad Awwal (IOSR Journal of Dental and Medical Sciences, 2014)
The study determined the availability of visual inspection with acetic-acid requirements for cervical cancer screening in secondary health care institutions of Kaduna state. A cross-sectional descriptive survey was used for the study. The study population comprises all nurses, midwives, and nurse-midwives working in all the secondary healthcare institutions of the state. The sample size used for the study was 300 using the Yamane sample size selection formula. The technique involved was stratified sampling method whereby the three existing senatorial zones served as strata. Each of the stratum was clustered according to the existing local government areas. A purposive sampling was further used to select nine local governments, three from each senatorial zone that have secondary health care institutions. A proportionate sampling was used to distribute questionnaire copies to the health workers. The instrument used for data collection was a questionnaire which has been modified to four point likert scale. Three hundred (300) questionnaire copies were administered out of which (297) were retrieved. The data collected was analyzed using one way analysis of variance (ANOVA) at 0.05 level of confidence to answer the hypotheses. A post-hoc scheffe test was further used to determine were th differences are. Findings from the study shows that VIA requirements are not available in the secondary health care institutions for cervical cancer screening with an aggregate mean score of (2.1458). There is a significant difference among the secondary health care institutions in the availability of VIA requirements to screen for cervical cancer in Kaduna state where (P<0.05). It is therefore recommended that the hospital management board should make provision of VIA requirements so that they can be available in the institutions for VIA screening services.